MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping

X

“Hurray! You have won the gift voucher. Redeem your points now."

X

                   

Show that the expression (ax-b)*(cx-d)/(bx-a)*(dx-c) can have all the values for real x if (a*a)-(b*b) and (c*c)-(d*d) have the same sign.

3 years ago

Share

Answers : (1)

                                        Hello student,
Please find the answer to your question below
Given(ax-b)*(cx-d)/(bx-a)*(dx-c)
=(acx2-(ad+bc)x+bd)/bdx2-(bc+ad)x+ac
=x2-((d/c)+(b/a))x+(bd/ac)/x2-((c/d)+(a/b))x+(ac/bd)
So by finding the discriminant of the equation from the above we can observe that
the expression (ax-b)*(cx-d)/(bx-a)*(dx-c) can have all the values for real x if (a*a)-(b*b) and (c*c)-(d*d) have the same sign.
11 months ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
(49)^7/2
 
 
(49)^7/2 = (7^2)^7/2=(7)^7= 823543
 
Kabilan Anbazhagan 15 days ago
The reminder when x^5 + kx^2 is divided by (x-1) (x-2) (x-3) contains no term in x^2. If teh value of k is -10a then a = ? Ans = 9
 
 
on dividing x^5 + kx^2 with (x-1) (x-2) (x-3) we get the remainder (k+90)x 2 -239x+150 as the remainder contains no x 2 terms …............k+90=0............k= -90= -10(9) first exp (x-1)...
 
noogler 14 days ago
which term of the G.P. 2,1,1/2,1/4... is 1/128?
 
 
You can do this simply by putting 1/128 as an exponential term in terms of (1/2) which is the common ratio. The first terrm is a=2, d=1/2, so you can either equate them directly equal to the...
  img
Ravi 9 months ago
 
t n =a*r n-1 where, a=initial term=2 n=nth term r=common ratio=1/2 1/128=2*(1/256)=2*(1/2) 8 =2*(1/2) n-1 Hence,n-1=8; …........n=9th term...
  img
Naveen Kumar 9 months ago
 
Of course we can have alternative ways to do it and I have given the answer which is one of them ….... Good luck for your exams!!!!!!!!!...
  img
Naveen Kumar 9 months ago
the image of the point (2,-1) with respect to the point (1,-4)
 
 
Let (x,y) be image of point (2,-1) (1,-4) will be mid point of (x,y) and (2,-1) x+2 = 2 y-1= -8 x=0 y= -7
  img
Harsh Patodia 4 months ago
IF SinA 1 + SinA 2 + SinA 3 = 1 then find the value of, cosA 1 + cosA 2 +cosA 3
 
 
Square both the sides and start manipulating. Note. take sinA3 to RHS
  img
Charchit Tailong 4 days ago
(log base e 2)(log base x 625) = (log base 10 16)(log base e 10) then x=?
 
 
Ans, x = 2; (Hint: Bring log base e 2 to the RHS and convert (log base e 10)/ (log base e 2) into 1/ log base 10 2.)
  img
Vijay Mukti one month ago
 
x=5 log e 2 log x 625=log 10 16 log e 10 log e 2 log x 625=log e 16 log a b log c a=log c b log e 2 log x 625=log e 2 4 log e 2 log x 625=4log e 2 loga x =x loga log x 625=4 625=x 4 x=5...
 
noogler one month ago
View all Questions »